Religion and Globalisation : general overview with special focus on the thought of Roland Robertson and the Roman Catholic Church's theological response to the process of globalisation - Serb, Dan Gheorghe (Department of Religious Studies, 2014)
Includes bibliographical references (leaves 91-98).